Micro rain radar (MRR) raw data measured at Neumayer Station (2023-07), links to files - Holger Schmithüsen; Lukas Muser (PANGAEA, 2025)
The meteorological observatory Neumayer continuously operates a vertically looking single column 24 GHz meteorological Doppler radar (METEK MRR-PRO) to monitor hydrometeors. The instrument essentially records radar reflectivity and Doppler velocity in 128 vertical range gates. The vertical resolution is set to 50m, hence the maximal altitude is 6400m; the temporal resolution is typically 1 second. The instrument was initially installed in January 2019 and is mounted on the roof of the Neumayer Station III. Since the station altitude changes slightly over time the instrument height above sea level can change over time too. This is documented in the netCDF variable "range:meters_to_center_of_first_gate", initially 65m. Since installation an interfering signal which could not be readily identified and removed disturbs the measurements in range gates 7 to 10, i.e. 370m to 520m. The disturbance can easily be identified and filtered for analysis of the data. This dataset contains the full raw data from the instrument. All data published here is left "as recorded", no quality control was applied. Still, some concatenation and temporal re-sorting was sporadically applied to homogenise the temporal file granularity. Any such operations are documented in the netCDF global attribute "history" of the respective files.
In: Schmithüsen, Holger (2025): Micro rain radar (MRR) raw data measured at Neumayer Station (2019-01 et seq) [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.981119